RT-AVTC: A Real-Time Audio-Visual Tone Correction Network Using Multimodal Deep Learning and Causal Convolution - Wang, Min; Duan, Yehui (Informatica, 2025)
Real-time feedback and robustness against environmental noise are critical challenges in computer-aided Chinese tone learning. This paper introduces RT-AVTC, a novel real-time audio-visual tone correction network designed to address those limitations through multimodal deep learning. The proposed architecture integrates a Multi-task Cascaded Convolutional Network (MTCNN) for audio-visual feature alignment, a causal convolution module and a Bidirectional Long Short-Term Memory (BiLSTM) network for robust temporal sequence classification, and a feedback module incorporating Dynamic Time Warping (DTW) for quantitative error analysis. The model was rigorously evaluated on the public LRS3 dataset. Experimental results demonstrated that the RT-AVTC model achieved a state-of-the-art accuracy of 94.26%, significantly outperforming strong baselines including Conformer and Whisper. Notably, in a challenging -5 dB signal-to-noise ratio environment, the multimodal approach yielded a 17.41% performance improvement over its audio-only counterpart. Furthermore, the error correction module provided targeted feedback, improving the average fundamental frequency (F0) curve deviation by over 55% for learners. With its high accuracy, real-time processing capability, and low computational overhead, the RT-AVTC framework presents a valuable and practical solution for effective computer-aided language learning.